A self-healing system for the soles of all rubber protective footwear - Adamus-Włodarczyk, Agnieszka; Irzmańska, Emilia; Szczepański, Grzegorz; Strąkowska, Anna; Rezmer, Sebastian; Dobrowolski, Mirosław (Wydawnictwo Politechniki Łódzkiej, 2022)
The objective of work was to improve the safety performance of protective footwear by increasing its service time using next-generation polymeric materials featuring autonomous self-healing mechanisms capable of repairing mechanical defects in a sole structure without an external intervention. The project innovation consists of using autonomous self-healing mechanisms in protective footwear to increase its service time and improve its safety performance in the workplace. Some mechanical defects naturally occur in the structure of personal protective equipment in the course of its normal use. While initially those defects are often not visible and difficult to detect, they may compromise polymeric materials and over time lead to permanent damage and shorter service times. The applied autonomous self-healing mechanisms (ASMs) have the capacity of immediate material regeneration without the external intervention. The first ASM involves a micro-encapsulated monomer released in the case of damage to fill the resulting defect in the sole. The other ASM involves the implementation of a network of channels supplying the monomer to the damaged area.
Keywords: protective footwear; self-healing materials; obuwie ochronne; materiały samoregenerujące